2018
DOI: 10.3389/fimmu.2018.02850
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Expression of sST2 in Early HIV Infected Patients Attenuated the IL-33 Induced T Cell Responses

Abstract: T cell responses were less functional and persisted in an exhausted state in chronic HIV infection. Even in early phase of HIV infection, the dysfunction of HIV-specific T cells can be observed in rapid progressors, but the underlying mechanisms are not fully understood. Cytokines play a central role in regulating T cell function. In this study, we sought to elucidate whether IL-33/ST2 axis plays roles in the regulation of T cell function in HIV infection. We found that the level of IL-33 was upregulated in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…The NLRP3 gene is located on the long arm of chromosome 1q44 and reacts to a diverse set of endogenous or exogenous stimuli [63]. NLRP3 has been linked to the pathogenesis of several diseases, including [1] metabolic disorders, such as type 2 diabetes [64], obesity [65], and autoimmune and inflammatory diseases [66][67][68]; neurological diseases [69]; and [2] diseases caused by viral pathogens, such as HIV [50], influenza A [70], and SARS-CoV [71]. SNPs in the NLRP3 gene have already been associated with a group of inflammatory disorders of genetic origin [32,72].…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 gene is located on the long arm of chromosome 1q44 and reacts to a diverse set of endogenous or exogenous stimuli [63]. NLRP3 has been linked to the pathogenesis of several diseases, including [1] metabolic disorders, such as type 2 diabetes [64], obesity [65], and autoimmune and inflammatory diseases [66][67][68]; neurological diseases [69]; and [2] diseases caused by viral pathogens, such as HIV [50], influenza A [70], and SARS-CoV [71]. SNPs in the NLRP3 gene have already been associated with a group of inflammatory disorders of genetic origin [32,72].…”
Section: Discussionmentioning
confidence: 99%
“…Current research has established some pathological mechanisms that are related to IRIS development, such as high viral loads, low baseline CD4+ T-cell counts (<50-100 cells/mm3) (Antonelli et al, 2010;Luetkemeyer et al, 2014) with high levels of CD4 activation and replication (Tibuŕcio et al, 2021), and short time intervals between TB treatment and cART (French et al, 2004;Chang et al, 2014;Tan et al, 2016). The genetic basis of host susceptibility to infectious diseases has received enormous attention (Fellay et al, 2009;Seaby et al, 2016;Wu et al, 2017). Highly polymorphic class I and II human leukocyte antigens (HLAs), killer-cell immunoglobulin-like receptor (KIR), cytokine genes, and genes involved in inflammation (inflammasome genes) are actively contributing factors that are associated with susceptibility and/or resistance to TB and HIV-1 infection (Kulkarni et al, 2008;Levy, 2009;Martin and Carrington, 2013;Pontillo et al, 2013;De Lima et al, 2016;Naranbhai and Carrington, 2017;Tsiara et al, 2018;de Sáet al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of novel aspects of this study, no other studies have investigated the role of lncRNA ANRIL in affecting the degradation of IL-33 in myocardial cells, which will enrich the literature and shed light on the underlying mechanism of lncRNA ANRIL in myocardial cell apoptosis after AMI. Numerous studies have shown that IL-33 could exert its functions by targeting ST2 in immune response or cancers [23,24]. IL-33 can recognize and interact with its specific receptor ST2 in immune cells, and anti-ST2 antibody reduced the effect of IL-33 on CD4 + T and CD8 + T cells during HIV-1 infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that IL-33 could exert its functions by targeting ST2 in immune response or cancers [23,24]. IL-33 can recognize and interact with its specific receptor ST2 in immune cells, and anti-ST2 antibody reduced the effect of IL-33 on CD4 + T and CD8 + T cells during HIV-1 infection [23]. IL-33/ST2 axis was involved in the activity of mast cells during colitis, and IL-33 promoted the percentage of IL-13/IL-22 producing T cells, which indicated that IL-33 regulated T cell differentiation and function [24].…”
Section: Discussionmentioning
confidence: 99%